2006
DOI: 10.1038/sj.onc.1209634
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of programmed cell death 4 in transforming growth factor-β1-induced apoptosis in human hepatocellular carcinoma

Abstract: The programmed cell death 4 (PDCD4) gene was originally identified as a tumor-related gene in humans and acts as a tumor-suppressor in mouse epidermal carcinoma cells. However, its function and regulatory mechanisms of expression in human cancer remain to be elucidated. We therefore investigated the expression of PDCD4 in human hepatocellular carcinoma (HCC) and the role of PDCD4 in human HCC cells. Downregulation of PDCD4 protein was observed in all HCC tissues tested compared with corresponding noncancerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
172
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(187 citation statements)
references
References 43 publications
10
172
0
1
Order By: Relevance
“…An anti-PDCD4 antibody was prepared by immunizing rabbits with a synthetic peptide corresponding to the N-terminal amino acid sequence (13). Anti-β-catenin, anti-Ecadherin, anti-Akt, anti-p44/42 MAP kinase and anti-β-actin antibodies were purchased from Cell Signaling Technology (Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An anti-PDCD4 antibody was prepared by immunizing rabbits with a synthetic peptide corresponding to the N-terminal amino acid sequence (13). Anti-β-catenin, anti-Ecadherin, anti-Akt, anti-p44/42 MAP kinase and anti-β-actin antibodies were purchased from Cell Signaling Technology (Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Homologs in mice (MA-3/TIS) (4,5), chickens (6,7) and rats (DUG) (8) have also been reported. The expression of the gene is modulated by many factors, including interleukins (9), retinoid (10), 12-O-tetradecanoylphorbol 13 acetate (TPA) (11,12), transforming growth factor (TGF)-β1 (13), growth factors (14,15), topoisomerase inhibitors (5) and the transcription factor myb (6,7), and is up-regulated in association with apoptosis (4,13). PDCD4 expression has been shown to be suppressed in many tumor tissues, such as lung cancers (16), pancreatic cancers (17), hepatocellular carcinomas (13), colon cancers (18), skin carcinomas (15), breast cancers (19) and glioma tissues (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pdcd4 was initially shown to suppress tumor development in an in vitro mouse keratinocyte model of tumor promotion (Cmarik et al, 1999). More recently, decreased expression of Pdcd4 has been implicated in the development and progression of human lung, colon, liver and breast cancer (Chen et al, 2003;Afonja et al, 2004;Zhang et al, 2006;Mudduluru et al, 2007). Pdcd4 expression is controlled by multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate PDCD4 has tumor suppressor activity. Loss of PDCD4 expression has been found in several types of human cancer cell lines [14], primary lung cancer [15], primary pancreatic cancer [16], hepatocarcinoma [17], colon carcinoma [18], and gliomas [19]. Recently, Wen et al [20] reported that compared to normal breast epithelial cells, PDCD4 expression is only slightly decreased in ductal carcinoma in situ samples, but is markedly decreased in invasive ductal carcinoma samples.…”
Section: Introductionmentioning
confidence: 99%